Institutional distances and equity-based entry modes of multinational companies in foreign countries - Silva, Fernando Jorge Moreira da (2022)
The decision to enter international markets is a central research topic in International Business - IB. Ownership is crucial when a firm decides to engage in foreign investments by making cross-border acquisitions. The extant literature has shown that ownership is contingent on the quality of the institutions at the target destination. Additionally, the concept of institutional distance and direction between origin and destination brought important advances in the IB literature. The conventional IB literature suggests that several country-specific factors influence the FDI. However, this opinion is not unanimous. Some researchers argue that the country is not the appropriate level of analysis, and the FDI phenomenon should be studied at the subnational level. This Ph.D. dissertation uses the theoretical support of neo-institutionalism to investigate the influence of institutional distances on ownership decisions in cross-border acquisitions. I analyze the existing literature on institutional distances and equity-based entry modes and focus the study on normative institutions, one of Scott's three institutional pillars (2001) that has not received much attention. I focus the study on the constructs of normative distance and direction to understand the influence on ownership decisions at the national level of analysis. At the subnational level, I analyze the impact of institutional distances on cross-border acquisitions in global cities, which attract MNCs and their subsidiaries due to their unique characteristics. The results reveal that the magnitude and direction of distance impact ownership choice. In large normative distances, the firm opts for partial acquisition when addressing more developed (positive direction) and less developed countries (negative direction). A partial acquisition was not expected from firms targeting more developed countries. Acquirers with high and low technology development make similar decisions, preferring total acquisitions at small normative distances and partial acquisitions at large normative distances in positive and negative directions. The results of this study do not confirm that acquirers prefer greater control over high technology development targets in institutionally less developed countries over large institutional distances. When analyzing firms' behavior at the subnational level, the results were similar to a country level, showing that acquirers' preference is for partial acquisition in most industries in global cities. This study advances our knowledge of the influence of normative institutional distances on ownership in cross-border acquisitions and the impact of distance direction in that relationship. Our in-depth analysis of the effects of normative institutional distances incorporating magnitude and direction has brought greater clarity to the role and influence of these institutions in MNC decisions. While the results shed more light on IB theory, they also motivate new research using the normative dimension of institutional distances in other contexts and MNC decisions. This study makes a second contribution by introducing the concept of global cities in studies on what influence institutions at the subnational level have on ownership decisions. Finally, its third contribution is to use neo-institutionalism as theoretical support for studying the effects of the asymmetry of institutional distances on ownership decisions in cross-border acquisitions.